Holistic Learning for Stimulation of Participant’s Basic Potential – Narrative Review - Salix Fini Maris (Westscience Press, 2025)
Common learning practices, which focuses more on academic achievement, diminishes the meaning of learning. Acquiring grades or knowledge only to emphasizes the intellect without addressing other aspects neglect the true potential of human abilities. Humans inherently possess basic potential that can dynamically grow and develop. This concept of basic potential is the basis for considering whether the intellect is the only attribute possessed by humans. Holistic learning is a foundation for learning that fully embraces human complexity: cognitive, social, emotional, and intellectual. This foundation relates to the basic potential that can be developed in students, such as sensory abilities, reasoning, empathy, and conscience. Based on this relationship, it shows that learning can be carried out using a multiple intelligence approach, which states that each person possesses diverse types of intelligence, so learning can be carried out in various ways. The application of multiple intelligence theory is consistent with experiential learning, where students with any intelligence approach can be facilitated through concrete, reflective, conceptual, and active learning. This study aims to formulate a practical framework for holistic learning using a multiple intelligences approach and experiential learning to enhance basic cognitive, intellectual, social, and emotional potential. Using the narrative review method, it was found that integrated learning can develop all dimensions of students, from cognitive to spiritual.